Cromossomos B no gênero Partamona (Hymenoptera: Apidae: Meliponini) : ocorrência, transmissão e origem - Machado, Diana de Paula (Universidade Federal de São Carlos, 2016)
Partamona (Schwarz, 1939) is a stingless bee genus which has as an interesting trait, the presence of B chromosomes in some species. These chromosomes were identified in six closely related species so far, all included in the cupira group, except P. helleri, which has an uncertain position in Partamona phylogeny, but it is possibly related to this group. We analyzed 894 colonies from 128 locations of thirteen species, using a SCAR marker specific for Partamona B chromosomes. The results enabled an increase in knowledge about species number with supernumerary chromosomes in this genus, including species from the pearsoni clade. The high number of colonies analyzed allowed to set the B chromosomes frequency on carrier species. A significant positive correlation between latitude and B chromosomes frequency was found in P. helleri, with higher frequency in north decreasing towards the south of the species distribution. The B chromosome transmission rate was estimated for three species that showed the highest frequencies of these chromosomes (P. helleri, P. cupira and P. rustica). The result was as expected for a regular meiotic behavior, which queens with one supernumerary chromosome have 50% chance to transfer the B chromosome to the offspring, suggesting an absence drive in these species. The Sequences obtained using SCAR primers had high quality and were different from those previously reported in another studies, showing no undefined sites, indicating greater effectiveness for sequencing using the internal primers designed in our laboratory. The comparison between obtained sequences revealed a high similarity between species, with only two haplotypes and no intraspecific differences, suggesting a single origin for Partamona B chromosomes. The sequence obtained for P. helleri was different from that obtained for the cupira clade species, suggesting that P. helleri did not transmit the B chromosomes to the other species, as previously suggested. The high frequency in some species and the presence in the pearsoni clade suggest a more complex 4 evolutionary history and an older origin than previously thought for Partamona B chromosomes.
Keywords: Cromossomos supranumerários; Abelhas sem ferrão; Marcador SCAR; Variação geográfica; Frequência; Acumulação; Origem interespecífica; Supernumerary chromosomes; Stingless bee; SCAR marker; Geographic variation frequency; Drive; Interespecific origin; CIENCIAS BIOLOGICAS::GENETICA